Characterization of leaf apoplastic peroxidases and metabolites in Vigna unguiculata in response to toxic manganese supply and silicon - Führs, Hendrik (Journal of experimental botany, 2009)
Previous work suggested that the apoplastic phenol composition and its interaction with apoplastic class III peroxidases (PODs) are decisive in the development or avoidance of manganese (Mn) toxicity in cowpea (Vigna unguiculata L.). This study characterizes apoplastic PODs with particular emphasis on the activities of specific isoenzymes and their modulation by phenols in the Mn-sensitive cowpea cultivar TVu 91 as affected by Mn and silicon (Si) supply. Si reduced Mn-induced toxicity symptoms without affecting the Mn uptake. Blue Native-PAGE combined with Nano-LC-MS/MS allowed identification of a range of POD isoenzymes in the apoplastic washing fluid (AWF). In Si-treated plants Mn-mediated induction of POD activity was delayed. Four POD isoenzymes eluted from the BN gels catalysed both H(2)O(2)-consuming and H(2)O(2)-producing activity with pH optima at 6.5 and 5.5, respectively. Four phenols enhanced NADH-peroxidase activity of these isoenzymes in the presence of Mn(2+) (p-coumaric=vanillic>>benzoic>ferulic acid). p-Coumaric acid-enhanced NADH-peroxidase activity was inhibited by ferulic acid (50%) and five other phenols (50-90%). An independent component analysis (ICA) of the total and apoplastic GC-MS-based metabolome profile showed that Mn, Si supply, and the AWF fraction (AWF(H(2)O), AWF(NaCl)) significantly changed the metabolite composition. Extracting non-polar metabolites from the AWF allowed the identification of phenols. Predominantly NADH-peroxidase activity-inhibiting ferulic acid appeared to be down-regulated in Mn-sensitive (+Mn, -Si) and up-regulated in Mn-tolerant (+Si) leaf tissue. The results presented here support the previously hypothesized role of apoplastic NADH-peroxidase and its activity-modulating phenols in Mn toxicity and Si-enhanced Mn tolerance